Exploring adolescents and young people's candidacy for utilising health services in a rural district, South Africa - Busisiwe Nkosi; Janet Seeley; Nothando Ngwenya; S. Lerato Mchunu; Dumile Gumede; Jane Ferguson; Aoife M. Doyle (BMC, 2019)
Abstract Background We use the 'candidacy framework' to describe adolescents' and young people's (AYP) experiences of health services in a rural KwaZulu-Natal district, South Africa. Methods A qualitative approach was used including group discussions, in-depth and key informant interviews with a purposive sample of AYP (n = 70), community leaders (n = 15), school health teams (n = 10), and health service providers (n = 6). Results Findings indicate tacit understanding among AYP that they are candidates for general health services. However, HIV stigma, apprehensions and misconceptions about sexual and reproductive health, and socio-cultural views which disapprove of AYP pre-marital sex undermine their candidacy for sexual and reproductive services. Conclusion Consideration and understanding of the vulnerabilities and reasons AYP exclude themselves will inform interventions to address their health needs. AYP's participation in the design of health services will increase their acceptability and encourage uptake of services.